Sex Differences in Fear of Falling among Older Adults with Low Grip Strength - Eunju LIM (Tehran University of Medical Sciences, 2016)
Background: Fear of falling is not only a risk factor for falls, but it is also an important clinical predictor of functional decline in older adults. This study identified sex differences in fear of falling and related factors in older adults with low grip strength. Methods: The data of 902 older adults from the 2012 Korean National Survey, conducted as a research project by the Korea Employment Information Service, were analyzed. Grip strength, activities of daily living, cognitive function, depressive symptoms, and fear of falling were assessed. Multiple regression analysis was performed by a simultaneous data entry method. Results: Fear of falling was greater in older women with low grip strength than in their male equivalents (P<0.001). Regression analysis showed that age, fall experience within the previous 2 yr, activities of daily living, and depressive symptoms collectively accounted for 15.3% (P<0.001) of the variance among men. Meanwhile, age, fall experience within the previous 2 yr, grip strength, activities of daily living, and depressive symptoms collectively accounted for 13.4% (P<0.001) of the variance among women. Conclusion: Thus, the predictors of fear of falling differ between older men and women with low grip strength. Therefore, sex differences must be considered when developing intervention strategies for reducing fear of falling in this demographic.